2021
DOI: 10.31234/osf.io/3d7ja
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testing for Audience Design: a short report

Abstract: In this short report, we present the results from a novel test set-up, aiming to track the practice of Audience Design (AD) in the reference production of Swedish speaking 7 year olds. AD is the conduct of altering one's communicative signal with the receiver of the signal in mind, so that they can easily infer its intended meaning. The results show a distinctive group that does not adapt production in the same manner as in a practice trial prompt for a third party without shared frame of mind. While we contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The referential production task was modified from two prior studies [ 3 , 5 ]. Its aim was to measure adolescents’ ability to adapt their referential expressions to the inferred world knowledge of their interlocutor.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The referential production task was modified from two prior studies [ 3 , 5 ]. Its aim was to measure adolescents’ ability to adapt their referential expressions to the inferred world knowledge of their interlocutor.…”
Section: Methodsmentioning
confidence: 99%
“…Building on results from 7-year-olds [ 3 ], we assumed that participants would name target referents in the known trials and that a relatively small number of trials would suffice to record that behaviour. We, however, expected that pragmatic development (taking place between age 7 through the investigated age groups in the present study) would be observed as variability in the unknown trials, i.e.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations